Labile hypertension and jogging: new diagnostic tool or spurious discovery?. Issue 6263 (14th February 1981) - Fitzgerald, W
Abstract : A labile hypertensive black man reviews his own personal history of hypertension, based on intensive self-study. The evidence suggests that aerobic isotonic exercise (jogging) depresses labile pressure values, forcing them down to near basal levels and preventing a rise to previous blood pressure levels for several hours.